Increasing binding of a transcription factor immediately downstream of the cap site of a cytomegalovirus gene represses expression. - Zhang, X Y (1995)
A closely related family of ubiquitous DNA binding proteins, called MDBP, binds with high affinity to two 14 base pair (bp) sites within the human cytomegalovirus immediate early gene 1 (CMV IE1) enhancer and with low affinity to one site beginning 5 bp downstream of the CMV IE1 transcription start point (+5 site). Unlike several cap position downstream MDBP sites in mammalian genes, these MDBP sites do not require cytosine methylation for optimal binding. Mutation of one of the enhancer MDBP sites to prevent MDBP recognition modestly increased the function of a neighboring CREB binding site in a transient transfection assay in the context of one promoter construct. A much larger effect on reporter gene expression (a 10-fold reduction) was seen when the low affinity MDBP recognition sequence at position +5 was converted to a high affinity site in a plasmid containing the CMV IE1 promoter upstream of the reporter gene. Evidence that the increased binding of MDBP at the mutant site is largely responsible for the observed results was provided by transfection experiments with this high affinity MDBP +5 site re-mutated to a non-binding site and by in vitro transcription assay.